2004
DOI: 10.1080/0003684042000266856
|View full text |Cite
|
Sign up to set email alerts
|

Economies of scale, school violence and the optimal size of schools

Abstract: This article argues that policy in relation to education has relied too extensively on the more easily measured costs of production to support a common conclusion of economies of scale in school and/or district size. It argues that there are external costs that increase with size but that can be measured less easily that offset this case. This would imply that the tendency within the education profession to advocate ever-larger school sizes is premature at best. To make the case, it models the choice of school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 8 publications
2
25
2
Order By: Relevance
“…School size may be an important factor in the frequency of bullying victimization, and, generally, students felt less safe in larger schools [49]. Some studies have suggested that larger schools have higher levels of violence [50], crime [51], and vandalism [52]. Perhaps these findings can be explained by the fact that increasing school size was related to decreasing student attachment to school, teachers, and extracurricular activities [53].…”
Section: Introductionmentioning
confidence: 70%
“…School size may be an important factor in the frequency of bullying victimization, and, generally, students felt less safe in larger schools [49]. Some studies have suggested that larger schools have higher levels of violence [50], crime [51], and vandalism [52]. Perhaps these findings can be explained by the fact that increasing school size was related to decreasing student attachment to school, teachers, and extracurricular activities [53].…”
Section: Introductionmentioning
confidence: 70%
“…Some studies have also found school connectedness to be inversely related to school size (Crosnoe, Johnson, & Elder, 2004;Kearney, 2008;McNeely et al, 2002;Thompson et al, 2006). Similar to school connectedness, some of the more recent literature on school size and violence has shown larger school size associated with higher rates of youth violence (Ferris & West, 2004;Kaiser, 2005;Leung & Ferris, 2008).Although sparse, some of the more recent literature on school size has indicated that as school size increases so do rates of youth violence. Some researchers (see Cotton, 1996aCotton, , 1996b have shown that behavioral and delinquency problems are more prevalent in larger schools.…”
mentioning
confidence: 90%
“…One particular variable, school size, has also been linked to youth violence. Some research has shown that incidents of youth violence are associated with increasing school size (e.g., Ferris & West, 2004;Kaiser, 2005;Leung & Ferris, 2008). However, empirical research is relatively sparse on the relationship between school size and youth violence, and especially between school size and school connectedness.…”
Section: Predicting Violence Vs Preventing Violencementioning
confidence: 99%
See 2 more Smart Citations